2021
DOI: 10.1108/ijif-04-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

Capital market and economic growth in Malaysia: the role of ṣukūk and other sub-components

Abstract: Purpose The purpose of this paper is to explore the effects of the capital market on economic growth by considering the role of ṣukūk (Islamic investment certificates) and other capital market sub-components in Malaysia between 1998 and 2018. Design/methodology/approach The empirical investigation is based on the autoregressive distributed lag (ARDL) cointegration bounds test. Findings The results reveal the prevalence of a long-run equilibrium relationship between capital market variables and economic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
2
10
0
1
Order By: Relevance
“…This study used time series data collected annually for quantitative analysis and did not have the minimum of 30 observations required for time series analysis. Tan and Shafi (2021) in another study explored the effects of the capital market on economic growth in Malaysia using quarterly data from quarter one of 1998 to quarter four of 2018. Economic growth was measured with per capita real GDP while the independent variable was measured with the following proxies of Sukuk conventional bonds, Stock market capitalisation, Total stock market turnover, real savings and growth rate of employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study used time series data collected annually for quantitative analysis and did not have the minimum of 30 observations required for time series analysis. Tan and Shafi (2021) in another study explored the effects of the capital market on economic growth in Malaysia using quarterly data from quarter one of 1998 to quarter four of 2018. Economic growth was measured with per capita real GDP while the independent variable was measured with the following proxies of Sukuk conventional bonds, Stock market capitalisation, Total stock market turnover, real savings and growth rate of employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies found that there is a long-run relationship between capital market variables or indicators and economic growth (Erasmus et al, 2021;Tan & Mohamad, 2021). The capital market has a significant positive impact on economic growth (Adesina-Uthman, 2020).…”
Section: Article Typementioning
confidence: 99%
“…Specifically, if sharia stocks grow, the economy will benefit because they become a source of funding for companies that are already listed on the stock exchange, boosting production, innovation, and resource allocation efficiency (Tan & Shafi, 2021) and sales of goods or services to consumers to drive the economy. In the 1910s, Schumpeter proposed that stock markets provide finance to businesses by allowing them to purchase new technologies, thereby promoting economic growth (Thaddeus et al, 2021).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In that case, one example is infrastructure, such as toll roads, which can increase transactions and economic mechanisms in Indonesia. Furthermore, the rise in outstanding corporate Sukuk indicates a high level of productivity in the form of more goods and services offered Tan & Shafi, 2021). Nneka (2022) asserted that Sukuk, as a long-term capital source, is critical for real economic sustainability and growth, as well as the stability of the financial system.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation